The Nervous System and Metabolic Dysregulation: Emerging Evidence Converges on Ketogenic Diet Therapy - Ruskin, David N.; Masino, Susan A. (Frontiers in Neuroscience, 2012)
A link between metabolism and brain function is clear. Since ancient times, epileptic seizures were noted as treatable with fasting, and historical observations of the therapeutic benefits of fasting on epilepsy were confirmed nearly 100 years ago. Shortly thereafter a high-fat, low-carbohydrate ketogenic diet debuted as a therapy to reduce seizures. This strict regimen could mimic the metabolic effects of fasting while allowing adequate caloric intake for ongoing energy demands. Today, ketogenic diet therapy, which forces predominantly ketone-based rather than glucose-based metabolism, is now well-established as highly successful in reducing seizures. More recently, cellular metabolic dysfunction in the nervous system has been recognized as existing side-by-side with nervous system disorders - although often with much less obvious cause-and-effect as the relationship between fasting and seizures. Rekindled interest in metabolic and dietary therapies for brain disorders complements new insight into their mechanisms and broader implications. Here we describe the emerging relationship between a ketogenic diet and adenosine as a way to reset brain metabolism and neuronal activity and disrupt a cycle of dysfunction. We also provide an overview of the effects of a ketogenic diet on cognition and recent data on the effects of a ketogenic diet on pain, and explore the relative time course quantified among hallmark metabolic changes, altered neuron function and altered animal behavior assessed after diet administration. We predict continued applications of metabolic therapies in treating dysfunction including and beyond the nervous system.